Ultra‐wideband antenna for wearable Internet of Things devices and wireless body area network applications. (12th March 2019) - Mustaqim, Muhammad; Khawaja, Bilal A.; Chattha, Hassan T.; Shafique, Kinza; Zafar, Muhammad J.; Jamil, Mohsin
Abstract: This paper presents a compact and planar ultra‐wideband (UWB) antenna, designed and characterized for the wearable Internet of Things (IoT) devices and wireless body area network (WBAN) applications. Two different substrates, ie, FR4 ( h  = 1.6 mm) and denim textile substrate ( h  = 1 mm), are used in the process of design and fabrication of the proposed antenna. The dimensions of the proposed antenna are 31 mm  ×  42 mm for FR4 substrate and 70 mm  ×  56 mm for denim textile substrate. The antenna structure consists of a rectangular radiating patch with two symmetrical staircase‐shaped slits. A reduced ground plane technique is used for the purpose of improving impedance bandwidth, which is further enhanced by the insertion of a small notch in the reduced ground plane which has improved the overall impedance matching characteristics of the proposed UWB antenna. The measured impedance bandwidth for S11  <  − 10 dB and gain of the FR4 and denim textile substrate UWB antennas are 7.71 GHz/5.12 dBi and 7.95 GHz/3.57 dBi, respectively. The ADS momentum simulator is used for antenna simulations, and the simulated and measured results are generally found in good agreements.